Membangun kompetensi menulis ilmiah siswa MA sebagai fondasi literasi akademik di perguruan tinggi - Syaharuddin Syaharuddin; Vera Mandailina; Abdillah Abdillah; Mahsup Mahsup; Sirajuddin Sirajuddin; Yunita Septriana Anwar (Penamas: Journal of Community Service, 2026)
The low level of scientific writing skills among high school students poses a challenge in building academic literacy readiness for college. This community service program aims to improve the scientific writing competencies of students at MA Nurul Islam Plus through outreach, training, technology-based mentoring, as well as evaluation and monitoring. The implementation method uses a participatory approach with a student-centered learning model that positions students as active participants in the learning process. The results of the activities demonstrate an improvement in students’ understanding of the basic structure of scientific papers, idea development, and the more systematic use of academic language. Program evaluation yielded an average response score of 77.29, indicating a positive category. The highest indicator was in the understanding of the use of Artificial Intelligence (AI) in scientific writing, while the lowest indicator was in the IMRAD structure, particularly the results and discussion sections. Although there were variations in ability among students, intensive mentoring was able to gradually improve scientific writing skills. Overall, this program effectively strengthened students’ academic literacy as a foundation for readiness to meet the demands of higher education. Literacy-strengthening programs based on mentoring and digital technology need to be continued on an ongoing basis within the madrasah environment.